Kiai Kampung and Transformational Leadership: A Model for Non-formal Education to Improve Community Quality of Life - Suhermanto, Suhermanto; Jasri, Moh. (Journal of Pesantren and Diniyah Studies, 2024)
This study aims to analyze the role of transformational leadership of village religious leaders (Kiai Kampung) in developing non-formal education and improving the community's quality of life. The research was conducted in Sumberrejo Village, Paiton District, Probolinggo Regency, East Java Province, focusing on five kiai who are prominent figures in the village. A qualitative approach with a case study method was employed. Data were collected through interviews, observations, and documentation, which were then analyzed through data collection, data reduction, data presentation, and conclusion. The study's results indicate that the transformational leadership applied by the Kiai Kampung in Sumberrejo Village is a driving force to achieve organizational goals and enhance the community's quality of life. The kiai utilizes four key characteristics of transformational leadership: (1) Idealized Influence/Charisma, (2) Intellectual Stimulation, (3) Individualized Consideration, and (4) Inspirational Motivation. Their leadership directs the development of community knowledge, with the kiai playing an active role in motivating, guiding, and inspiring individuals to achieve shared goals and visions. Direct involvement and close interaction between the kiai and the community significantly support achieving these goals. Through leadership based on close social interactions and continuous development, the quality of life in Sumberrejo Village, particularly in education and social empowerment, has experienced significant improvement. This study demonstrates that kiai kampung leadership can be a key factor in community empowerment at the local level.